Efektifitas William’s Flexion Exercise Dengan Kompres Hangat Terhadap Dismenorea Primer di MAN 2 Jember - Dewi, Mega Sylviana; Restanty, Dian Aby; Karnasih, I Gusti Ayu (Malang Journal of Midwifery (MAJORY), 2020)
The incidence of menstrual pain (dysmenorrhoea) in MAN 2 Jember was 61.6%. This study aims to determine the difference in the effectiveness of William's flexion exercise with warm compresses on primary dysmenorrhoea pain. The research design used a Quasi-Experiment with a non-equivalent pretest-posttest design. The population consisted of 37 female students and the sample taken was a sample that met the inclusion criteria contained in chapter three as many as 34 students, the sample was divided into 2 treatment groups, namely 17 students were treated with William's Flexion exercise and 17 students were treated with warm compresses. This research uses simple random sampling technique. The research instrument used the Standard Operational Procedure and Numeric Rating Scale, with the Wilcoxon match pairs test and the Mann Whitney U test. Wilcoxon test results p-value 0.000, and an error level of 5% (2-sided test), which means that there is a difference in the level of dysmenorrhoea pain before and after being given warm compresses and William's flexion exercise and the results of the Mann Whitney U test obtained Z value = -1.285 with an error rate of 5%, then -1.96 <-1.285 <+1.96, meaning that there is no difference in the effectiveness of William's Flexion Exersice with warm compresses on primary dysmenorrhoea. The two methods are equally effective in reducing primary dysmenorrhoea pain, although there are slight differences. Where a warm compress is better at reducing the pain intensity of primary dysmenorrhoea. Keywords: Warm Compress, William's Flexion Exercise, Primary Dysmenorrhoea